3D-Forming and Autodesk Autocad at the Initial Stage of Engineering Training of Specialists in Technical Areas - V. Telegin, V; V. Telegin, I; S. Stepanov, A (International Journal of Engineering and Technology, 2018)
Descriptive geometry is one of the disciplines that for a long time is the basis for training engineers of various specializations. However, with the advent of modern computer 3D technologies, the place and role in engineering of many traditional disciplines requires rethinking. The article is devoted to the integration of methods of descriptive geometry into the educational process of preparing students of higher educational institutions.Â Â